2020
DOI: 10.1111/are.15091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of olive leaf extract (Olea europaea Leecino) on growth, haematological parameters, immune system and carcass composition in common carp (Cyprinus carpio)

Abstract: In this study, the effects of olive leaf extract on growth, haematological parameters, immune system and carcass composition in common carp were examined. In this research, 180 common carp (32.26 ± 1.01 g) were randomly distributed to nine fibreglass tanks. The fish were fed a diet with 200 mg/kg olive leaf extract (group 1), 400 mg/kg olive leaf extract (group 2), and basal food (control group) for 75 days. At the end of the experiment, WG, SGR and PER values were significantly higher in the groups fed the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
3
10
1
Order By: Relevance
“…Indeed, this was also found in rainbow trout ( Onchorynchus mykiss ) after a 6-week feeding trial with an olive waste cake ( Hoseinifar et al, 2020 ). A similar response in terms of growth was also reported in common carp ( Cyprinus carpio ) fed with an olive leaf extract-supplemented diet ( Zemheri-Navruz et al, 2020 ; Sokooti et al, 2021 ). In contrast, growth performance values, such as BW gain and standard growth rate, or feed utilization were not affected in rainbow trout fed with a diet containing different levels of olive leaf extract for 60 days ( Baba et al, 2018 ).…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, this was also found in rainbow trout ( Onchorynchus mykiss ) after a 6-week feeding trial with an olive waste cake ( Hoseinifar et al, 2020 ). A similar response in terms of growth was also reported in common carp ( Cyprinus carpio ) fed with an olive leaf extract-supplemented diet ( Zemheri-Navruz et al, 2020 ; Sokooti et al, 2021 ). In contrast, growth performance values, such as BW gain and standard growth rate, or feed utilization were not affected in rainbow trout fed with a diet containing different levels of olive leaf extract for 60 days ( Baba et al, 2018 ).…”
Section: Discussionsupporting
confidence: 76%
“…In the current captive breeding process of Chinese sturgeon, we can feed a mixture of natural foods and formula diets in different proportions with feed additives. In a previous study, the addition of appropriate olive leaf extract to the feed improved growth performance and health of the common carp (Cyprinus carpio) [31].…”
Section: Discussionmentioning
confidence: 91%
“…Green tea administration also showed no obvious effect on growth of rainbow trout [ 33 ]. Nevertheless, other studies indicated that dietary supplementation with olive waste cake and olive leaf extract can have a positive effect on the growth performance of rainbow trout and common carp [ 34 , 35 ]. Interestingly, our experiment found that the supplementation of largemouth bass diet with 0.05% of a PFA containing plant extracts derived from olive and green tea, having main active components triterpenes (maslinic acid and oleanolic acid) and polyphenols, can not only significantly improve growth performance of largemouth bass but can also regulate mammalian target of rapamycin (mTOR) and AKT (serine/threonine kinase, also known as protein kinase B) to promote protein deposition.…”
Section: Discussionmentioning
confidence: 99%